Antibacterial Activity Test of Combined Extracts of Guava Leaves (Psidium guajava L.) and Celery Stalks (Apium graveolens L. var. dulce) Against Staphylococcus aureus and Escherichia coli - Dhiyanti Ika Salamah; Putri Eka Sari; Indri Astuti Handayani (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Antibiotic resistance in pathogenic bacteria such as Staphylococcus aureus and Escherichia coli has become a critical global health concern. Flavonoids, tannins, and saponins in guava leaves (Psidium guajava L.) and celery stalks (Apium graveolens L. var. dulce) suggest their potential as natural antibacterial agents, but studies on their combined effectiveness remain limited. This study aimed to evaluate the synergistic effect, optimal concentration, and antibacterial activity of combined guava leaf and celery stalk extracts against gram-positive and gram-negative bacteria. This laboratory-based experimental study used the maceration method with 96% ethanol as the solvent. Antibacterial activity was assessed through the disc diffusion method against S. aureus and E. coli. The study tested 40% single extracts and combinations in ratios of 1:1, 1:2, and 2:1. The findings showed that the combination did not produce a synergistic effect. The highest antibacterial activity against S. aureus was observed in the 2:1 combination, producing an inhibition zone of 11.06 mm, although still lower than the 40% guava leaf extract (11.75 mm). In E. coli, all treatments demonstrated weak activity, with the 1:1 combination yielding the highest inhibition zone of 3.74 mm. Statistical analysis using ANOVA and Games-Howell indicated a significant difference for S. aureus, while the Kruskal-Wallis test showed no significant difference for E. coli (p > 0.05). The combination of guava leaf and celery stalk extracts did not exhibit a synergistic effect. The 2:1 combination was the most effective against S. aureus, while the 1:1 combination showed limited activity against E. coli.